2023
DOI: 10.7759/cureus.33630
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Various Modalities in the Treatment of Early Knee Osteoarthritis: An Unsolved Controversy

Abstract: IntroductionOsteoarthritis (OA) of the knee is a common degenerative disease, relatively more prevalent among middleaged people. It is one of the major reasons for walking-related disability. Recently, early knee OA has been seen as an imperative concern in many younger patients who struggle with the disabling effect of pain and management is extremely speckled. Degenerative changes such as loss of cartilage, subchondral bone changes, synovial inflammation, and meniscal degeneration are seen in OA. Symptoms ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…It can be observed that the contact angle varied only marginally even after 10 n-hexane washes. These results suggest that in future communications the coated fabric can be suitably employed for an oil water separation process 48 using n-hexane.…”
Section: Durability Study Of Polybenzoxazine-coated Cotton Fabricmentioning
confidence: 86%
“…It can be observed that the contact angle varied only marginally even after 10 n-hexane washes. These results suggest that in future communications the coated fabric can be suitably employed for an oil water separation process 48 using n-hexane.…”
Section: Durability Study Of Polybenzoxazine-coated Cotton Fabricmentioning
confidence: 86%
“…The chronic pain in KOA patients is not necessarily related to damage to the peripheral muscular system, but rather to neuroplastic changes in painrelated circuits that result in maladaptive neuroplasticity and lead to a perpetuation of pain [16]. The neuroplasticity changes in response to constant peripheral pain and less intracortical inhibition, which leads to enhance the levels of pain and dysfunction [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the sufficient inherent stability of the TF joint (provided by bone shape, ligaments, and antagonistic muscles), non-traumatic disorders are uncommon in young individuals. Insidious and progressive degeneration generally occurs after 53 years of age [ 4 ]. In contrast, the PF joint is inherently unstable.…”
Section: Introductionmentioning
confidence: 99%